Descripción del uso de cámaras multiespectrales en el diagnóstico de cultivos - Montero Zapata, Javier Elías (2022)
Highly technical agriculture uses a wide variety of techniques and external inputs to obtain optimal crop yields. It is interesting to have a tool that helps to visualize the different problems of the plants. At the beginning, to solve certain problems in plantations, the capture of images was carried out every 8 days, because the satellite took that long to return to the same point. Later, drones emerged, which are equipment propelled by several propellers and that can mount various types of cameras. The use of drones with the aim of diagnosing crop states is done by capturing aerial images. Multispectral imaging systems and techniques are located in drones and are small in size. From the multispectral images captured by this type of sensor, it is possible to determine different vegetation indices that indicate the physiology of plants. Multispectral cameras are characterized by capturing information between 3 and 7 bands. The information described in the investigation was carried out through the technique of analysis, synthesis and summary, in order for the reader to know about the importance of multispectral cameras. Due to the aforementioned, it was found that multispectral systems allow the capture of various light spectra and provide phenotyping, crop health mapping, irrigation management, fertilizer management, disease identification, species differentiation, among others. The main index used in crop monitoring is the NDVI index, since the use of different types of indices in the use of drones will allow us to increase crop production.